Using illustrations to make decisions on the most appropriate qualitative research methodology: the industry 4.0 scenario - Janis, Ilyana; Alias, Maizam; Zulkipli, Muhammad; Muhammad-Sukki, Firdaus (SAGE Publications, 2020)
Industry 4.0 is viewed as a complex scenario. This complex scenario could be interpreted using illustrations such as sketches or drawings. Ideally, sketches and drawings are useful in illustrating complexity and multiple abstracts from observed social reality. The use of illustrations allows novice qualitative researchers to explore observed social reality in depth with less linear insight. However, few scholars mention the use of illustrations at the research planning stage because most sketches and drawings have been used as tools during data collection merely to understand an interviewee’s perspective. Therefore, this article aims to demonstrate the use of illustrations as a tool to facilitate the research process from problem identification to the selection of the qualitative research methodology. Five specific purposes of illustration that significantly contribute to the body of knowledge for effective decision making and are useful tools in delivering information are demonstrated in this article. Based on the illustrations demonstrated in this article, the most appropriate qualitative research methodology is the case study. Overall, the proposed use of illustrations can assist a novice qualitative researcher in determining the appropriate epistemological and ontological stances, as well as their methodology and method, more effectively.